ANATOMICAL VARIATIONS IN RECURRENT LARYNGEAL NERVES IN THYROID SURGERY - NAEEM, MM; ANWAR, MI; KHAWAR, A; AFSAR, B; SIKANDAR, S; GHAFFAR, H (Biological and Clinical Sciences Research Journal, 2024)
The recurrent laryngeal nerve (RLN) is a critical structure encountered during thyroid surgery, with its injury posing risks of complications such as vocal cord paralysis and hoarseness. Anatomical variations in the RLN are known to occur, making it crucial for surgeons to understand and anticipate these variations to avoid inadvertent nerve injury. This study aims to identify and document the anatomical variations in RLNs in patients undergoing thyroid surgery to enhance surgical safety and outcomes. Objective: To identify the anatomical variations of the recurrent laryngeal nerves (RLNs) in patients undergoing thyroid surgery and assess their clinical relevance in preventing postoperative complications. Methods: A prospective observational study was conducted in the General Surgery Department of Sheikh Zayed Hospital, Lahore, from August 2023 to August 2024. A total of 100 patients undergoing total or subtotal thyroidectomy or right/left lobectomy for conditions including thyroid cancer, multinodular goiter, and solitary adenoma were included. Macroscopic examination of the RLN’s original structure, bifurcations, and directional variations was performed during surgery. Lateral, inferior, and superior dissection of the RLNs was conducted under general anesthesia. The study’s primary outcomes were the incidence of different anatomical variations in the RLN and their bifurcations to the larynx. Postoperative complications such as dyspnea and hoarseness were also monitored. Results: Of the 100 patients studied, 107 RLNs were identified, with variations categorized into six types. Type I RLNs were observed in 66.9% of cases, with 50.5% on the right side and 49.5% on the left. Type II RLNs were noted in 26.3% of cases, evenly distributed between right and left sides (50% each). Type III nerves were predominantly left-sided (62.5%) compared to right-sided (37.5%). Types IV, V, and VI were only observed on the right side. No significant difference in variation patterns was observed between the right and left sides (p>0.05). Importantly, none of the patients developed postoperative complications such as dyspnea or hoarseness. Conclusion: The study identified six distinct types of anatomical variations in the recurrent laryngeal nerve during thyroid surgery, with variations involving one or more branches. Awareness of these variations is crucial for surgeons to avoid nerve injury and ensure better surgical outcomes. Vigilance during dissection, particularly in recognizing these variants, is essential in preventing postoperative complications.